The Influence of Relationship Marketing and Mobile Banking Service Quality on Bank Syariah Indonesia Customer Loyalty Through Corporate Social Responsibility (CSR) as an Intervening Variable - Esti Musriana; Rifaatul Indana (Genius: Jurnal Ekonomi Dan Manajemen, 2025)
This research aims to analyze the influence of Relationship Marketing and Mobile Banking service quality on Bank Syariah Indonesia customer loyalty through Corporate Social Responsibility. The methodology used in this research uses a quantitative approach with Nonprobability Sampling data collection techniques. The research results show that the Corporate Social Responsibility variable has no effect on Loyalty, Mobile Banking Service Quality has an effect on Corporate Social Responsibility, Mobile Banking Service Quality has an effect on Loyalty, Relationship Marketing has an effect on Corporate Social Responsibility, Relationship Marketing has an effect on Loyalty, Mobile Banking Service Quality has no effect influences loyalty through Corporate Social Responsibility, Relationship Marketing influences loyalty through Corporate Social Responsibility. This research only focuses on IMAPSI Sharia Banking students in the Yogyakarta region, therefore to produce comprehensive research for future researchers to expand the sample coverage to IMAPSI Sharia Banking students in the national region.